Treatment Patterns and Outcomes of Women with Symptomatic and Asymptomatic Breast Cancer Brain Metastases: A Single‐Center Retrospective Study. (21st September 2021) - Gao, Yizhuo Kelly; Kuksis, Markus; Id Said, Badr; Chehade, Rania; Kiss, Alex; Tran, William; Sickandar, Faisal; Sahgal, Arjun; Warner, Ellen; Soliman, Hany; Jerzak, Katarzyna J.
Abstract: Background: Breast cancer is the most common cancer among women worldwide and the second leading cause of brain metastases (BrM). We assessed the treatment patterns and outcomes of women treated for breast cancer BrM at our institution in the modern era of stereotactic radiosurgery (SRS). Materials and Methods: We conducted a retrospective analysis of women (≥18 years of age) with metastatic breast cancer who were treated with surgery, whole brain radiotherapy (WBRT), or SRS to the brain at the Sunnybrook Odette Cancer Centre, Toronto, Canada, between 2008 and 2018. Patients with a history of other malignancies and those with an uncertain date of diagnosis of BrM were excluded. Descriptive statistics were generated and survival analyses were performed with subgroup analyses by breast cancer subtype. Results: Among 683 eligible patients, 153 (22.4%) had triple‐negative breast cancer, 188 (27.5%) had HER2+, 246 (36.0%) had hormone receptor (HR)+/HER2−, and 61 (13.3%) had breast cancer of an unknown subtype. The majority of patients received first‐line WBRT ( n = 459, 67.2%) or SRS ( n = 126, 18.4%). The median brain‐specific progression‐free survival and median overall survival (OS) were 4.1 months (interquartile range [IQR] 1.0–9.6 months) and 5.1 months (IQR 2.0–11.7 months) in the overall patent population, respectively. Age >60 years, presence of neurological symptoms at BrM diagnosis, first‐line WBRT, and HER2− subtype were independently prognostic for shorter OS. Conclusion: Despite the use of SRS, outcomes among patients with breast cancer BrM remain poor. Strategies for early detection of BrM and central nervous system–active systemic therapies warrant further investigation. Implications for Practice: Although triple‐negative breast cancer and HER2+ breast cancer have a predilection for metastasis to the central nervous system (CNS), patients with hormone receptor–positive/HER2− breast cancer represent a high proportion of patients with breast cancer brain metastases (BrM). Hence, clinical trials should include patients with BrM and evaluate CNS‐specific activity of novel systemic therapies when feasible, irrespective of breast cancer subtype. In addition, given that symptomatic BrM are associated with shorter survival, this study suggests that screening programs for the early detection and treatment of breast cancer BrM warrant further investigation in an era of minimally toxic stereotactic radiosurgery. Abstract : Despite advances in treatment, the prognosis of patients with breast cancer brain metastasis remains poor. This article assesses treatment patterns and outcomes of such patients in the modern era of stereotactic radiosurgery.